Adsorption and immobilization method for heavy metal ions in water and geopolymer cementing material

By using carbonized concrete micro powder to adsorb heavy metal ions and combining them with blast furnace slag and other materials for alkali excitation molding, the problem of low treatment efficiency of high-concentration heavy metal contaminated wastewater in the prior art is solved, and efficient adsorption and fixation and high compressive strength gelled material preparation is achieved.

CN119841388AActive Publication Date: 2025-04-18GUANGZHOU UNIVERSITY
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202510081902.0
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-17
Publication Date
2025-04-18
Estimated Expiration
2045-01-17

AI Technical Summary

Technical Problem

When the prior art treats high-concentration heavy metal contaminated wastewater, the alkali excitation reaction process is hindered, the fluidity is poor, and the curing efficiency and compressive strength are insufficient, which limits its application scope.

Method used

Carbonized concrete powder is used to adsorb heavy metal ions in the water, and mix it with granulated blast furnace slag and other materials, and cure and mold it with alkali exciter to form a gelled material with a three-dimensional crosslinking structure.

Benefits of technology

It realizes efficient adsorption and fixation of high-concentration heavy metal polluted wastewater, and the resulting geological polymer gelling material has high compressive strength and good environmental durability, reducing the environmental diffusion of heavy metals.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119841388A_ABST
    Figure CN119841388A_ABST
Patent Text Reader

Abstract

The invention discloses a method for adsorbing and fixing heavy metal ions in water and a method for preparing a geopolymer cementing material, and belongs to the field of environmental protection engineering and material engineering.The method comprises the following steps that carbonized micro powder is used for adsorbing the heavy metal ions in the water; the carbonized micro powder is obtained by carbonizing concrete micro powder in a carbon dioxide atmosphere; mixing the carbonized micro powder adsorbing the heavy metal ions with one or more of granulated blast furnace slag, gypsum and steel slag to obtain a solid material; mixing the solid material with an alkali activator, and curing and molding; according to the method, the curing amount of heavy metal can be remarkably increased, the curing efficiency can reach 99.99%, meanwhile, the prepared geopolymer has excellent mechanical properties, can be used in the fields of low-cost green building materials or solid waste landfill and the like, has remarkable environmental and economic benefits, and well solves the problem of high-concentration heavy metal pollution abatement.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the fields of environmental protection engineering and material engineering, and in particular to a method for adsorbing and fixing heavy metal ions in water and a geopolymer gelling material. Background Art

[0002] Over the past 30 years, the heavy metal industry has experienced rapid expansion. Due to the irregular and excessive use of industrial wastewater in industrial manufacturing, mining, and domestic use, a large amount of heavy metal waste has been discharged into the environment, posing a serious threat to human health and the living environment, and has become a very challenging environmental issue.

[0003] Solidification / stabilization (S / S) technology has been widely proven to be an efficient, fast and economical method for heavy metal treatment. Traditional silicate cement is a good curing agent and binder. However, the production of silicate cement will produce a large amount of carbon dioxide emissions and energy consumption, thereby exacerbating the greenhouse effect. Similar to silicate cement, geopolymers also exhibit excellent heavy metal ion fixation ability, and the production of geopolymers uses solid waste materials, which is lower in cost and does not aggravate the greenhouse effect. Han Fenglan et al. in "Solidification / stabilization mechanism of Pb(II), Cd(II), Mn(II) and Cr(III) in fly ash based geopolymers" (Construction and Building Materials, 2018, 160: 818-827) used fly ash as raw material to prepare geopolymers under alkali excitation conditions for the solidification of heavy metal Pb 2+ 、Cd 2+ , Mn 2+ and Cr 3+ , studies have shown that when Pb 2+ 、Cd 2+ , Mn 2+ and Cr 3+ When the content of Cd is 1.5wt%, the curing efficiency reaches 99.92-99.98%, and the 28-day compressive strength of the sample reaches a maximum of 49.34MPa; Ji Zehua et al. 2+ ,Pb 2+ and Zn 2+ )and anions(AsO4 3- and Cr2O7 2-)in wastes-based geopolymer" (Journal of Hazardous Materials, 2020, 384:121290), drinking water treatment residue (DWTR) and blast furnace slag (GBFS) were used as the main raw materials to prepare geopolymers under alkali-activated conditions for the immobilization of Cd 2+ , Pb 2+ and Zn 2+ The results show that when Cd 2+ , Pb 2+ and Zn 2+ When the dosage is below 4wt%, the curing efficiency reaches 92.34%-100%, and the 7-day compressive strength of the sample reaches up to 16MPa. Existing studies have shown that alkali-based polymers are highly efficient in curing heavy metal ions, but the maximum concentration of curable heavy metal ions is generally low, usually limited to 0.5wt% to 4wt%. When the heavy metal ion dosage is high, it will seriously hinder the alkali-induced reaction process and cause poor fluidity, which limits its application in the treatment of high-concentration heavy metal pollution.

[0004] On the other hand, the current resource utilization rate of construction waste in China is only 5%, and most of the construction solid waste is directly discarded or landfilled. Waste concrete is the main component of construction waste. The waste concrete powder with a particle size of less than 0.15 mm produced during the recycling process is still mainly used for landfill or as a filling material and has not yet been effectively utilized. Waste concrete powder is rich in a large number of hydration products, such as hydrated calcium silicate. These mineral components have high carbonization activity and can react with CO2 to reconstruct mineral components to generate substances such as calcium carbonate, amorphous silica gel and aluminum gel. The carbonized powder product can be used to effectively adsorb and remove heavy metal ions in wastewater, and the carbonized powder adsorbed with heavy metals can be further solidified by alkali excitation technology. Summary of the invention

[0005] In view of the above problems, the present invention adopts the solidification / stabilization technology of geopolymers to provide a method for adsorbing and fixing heavy metal ions in water and a geopolymer gelling material, thereby achieving efficient adsorption and fixation of high-concentration heavy metal-contaminated wastewater, and preparing a geopolymer gelling material with high compressive strength. The geopolymer gelling material has low preparation cost, is low-carbon and environmentally friendly, and can be widely used in fields such as solid waste landfill.

[0006] The purpose of the present invention is achieved by the following technical solutions:

[0007] A method for adsorbing and fixing heavy metal ions in water comprises the following steps:

[0008] (1) Adsorbing heavy metal ions in water with carbonized powder; the carbonized powder is obtained by carbonizing concrete powder in a carbon dioxide atmosphere, and the concrete powder is obtained by grinding hydrated cement, such as grinding cement after natural curing into powder, such as grinding waste concrete into powder, and such as grinding waste concrete with coarse aggregate and / or fine aggregate into powder;

[0009] (2) mixing the carbonized micropowder after adsorbing heavy metal ions with one or more of granulated blast furnace slag, gypsum, and steel slag to obtain a solid material;

[0010] (3) mixing the solid material with an alkali activator and curing and forming the solid material;

[0011] In some preferred embodiments, the heavy metal ions are one or more of lead ions, zinc ions, and copper ions.

[0012] In some preferred embodiments, the particle size of the concrete powder is less than 125 μm.

[0013] In some preferred embodiments, the concrete fine powder has a CaO content of not less than 48.28%, a SiO2 content of not less than 15.27%, and an Al2O3 content of not less than 4.32% by weight.

[0014] In some preferred embodiments, the carbonization conditions are: humidity 70±3%, temperature 20±2°C, carbon dioxide concentration 20±3%, and carbonization time 7 days.

[0015] In some preferred embodiments, the granulated blast furnace slag is S95 grade slag, and the median particle size D50 is 12.06 μm.

[0016] In some preferred embodiments, the mass ratio of the carbonized micropowder after adsorbing heavy metal ions in the solid material is 30-70%.

[0017] In some preferred embodiments, the alkaline activator comprises a mixture of sodium hydroxide solution and water glass, the modulus of which is 1-2 and the Na2O content is 3-6 wt%.

[0018] In some preferred embodiments, the water-cement ratio of the solid material to the alkali activator is 0.38-0.45.

[0019] In some preferred embodiments, the curing temperature in step (3) is 20±2° C. and the relative humidity is >95%.

[0020] Another object of the present invention is to provide a geopolymer gelling material, wherein the geopolymer gelling material is prepared by the above-mentioned adsorption and fixation method.

[0021] The beneficial effects of the present invention are:

[0022] The present invention utilizes the huge adsorption capacity of carbonized concrete powder to first adsorb heavy metal ions in wastewater, and then utilizes its high alkali activation activity to react with precursors such as slag to generate a gelling material with a three-dimensional cross-linked structure, providing superior structural strength for geopolymers. In this process, a large amount of heavy metals are introduced into the geopolymer system, and the heavy metal ions can form certain special phases in the matrix phase by generating certain chemical bonds with the aluminum silicate skeleton in the formation of the geopolymer structure; in addition, the gel network of the geopolymer has good inclusive performance, and can stably embed heavy metals and their generated precipitation into its microstructure, thereby effectively limiting the migration ability of heavy metals and the possibility of secondary reactions, and improving the environmental durability and safety of the material. The geopolymer solidified body after the heavy metal is solidified by the present invention has excellent mechanical properties, and can solidify a large amount of heavy metals, and the leaching concentration of each heavy metal is far below the limit, reducing the environmental diffusion of heavy metals; the present invention utilizes industrial by-products, effectively reducing the demand for expensive adsorption materials and waste treatment costs, and can convert waste into valuable building materials, reducing the energy consumption and carbon emissions of new material production, meeting the standards of environmental protection and sustainable development, and improving environmental sustainability. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] The present invention is further described using the accompanying drawings, but the embodiments in the accompanying drawings do not constitute any limitation to the present invention. A person skilled in the art can obtain other drawings based on the following drawings without creative work.

[0024] Figure 1 It is a flow chart of the adsorption and solidification method of heavy metal ions in wastewater according to the present invention;

[0025] Figure 2 is the unconfined compressive strength result of the geopolymer cementitious material specimen prepared in Example 1 of the present invention;

[0026] Figure 3 is the unconfined compressive strength result of the geopolymer cementitious material specimen prepared in Example 2 of the present invention;

[0027] Figure 4 is the unconfined compressive strength result of the geopolymer cementitious material specimen prepared in Example 3 of the present invention;

[0028] Figure 5 is the toxicity leaching result of the geopolymer gelling material specimen prepared in Example 1 of the present invention;

[0029] Figure 6 is the toxicity leaching result of the geopolymer cementitious material specimen prepared in Example 2 of the present invention;

[0030] Figure 7 is the toxicity leaching result of the geopolymer gelling material specimen prepared in Example 3 of the present invention;

[0031] Figure 8 It is the toxicity leaching result of the geopolymer gelling material specimen prepared in Comparative Example 1 of the present invention;

[0032] Fig. 9 It is the unconfined compressive strength result of the geopolymer cementitious material specimen prepared in Comparative Example 2 of the present invention;

[0033] Fig.10 It is the toxicity leaching result of the geopolymer gelling material specimen prepared in Comparative Example 2 of the present invention;

[0034] Fig.11 It is the unconfined compressive strength result of the geopolymer cementitious material specimen prepared in Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0035] The present invention is further described in conjunction with the following examples.

[0036] Example 1

[0037] This embodiment relates to a method for adsorbing and solidifying heavy metal ions in wastewater, and also relates to a method for preparing a geopolymer gelling material, comprising the following steps:

[0038] (1) grinding cement naturally cured for 7 days in a ball mill to a particle size of less than 125 μm to obtain concrete powder, wherein the concrete powder has a CaO content of 48.28%, a SiO2 content of 15.27%, and an Al2O3 content of 4.32%, and then carbonizing the concrete powder for 7 days under the conditions of a humidity of 70±3%, a temperature of 20±2° C., and a carbon dioxide concentration of 20±3%, wherein the grayish white concrete powder is transformed into pure gray carbonized concrete powder after carbonization; The carbonized concrete powder and the lead-containing wastewater are added into a glass container at a ratio of 10 g:1 L, the concentration of lead ions in the wastewater is 1600 mg / L, and the mixture is shaken in a shaker at 25° C. and 200 rpm for 10 minutes, and then filtered in a vacuum filtration device using a 30 μm PP polypropylene filter membrane to obtain powder and treated wastewater, and the carbonized concrete powder adsorbing lead ions obtained by filtration is dried in an oven at 60° C. for 4 hours, and the treated wastewater is used to test the concentration of heavy metal ions;

[0039] (2) water, NaOH and water glass are mixed to prepare an alkaline activator with a modulus of 1.2 and a Na2O content of 5%, and the mixture is allowed to stand for 24 hours for use; the carbonized concrete powder adsorbing lead ions and granulated blast furnace slag of equal weight (50%:50%, wherein theoretically, heavy metals account for about 7% of the ash mass) dried in step (1) are added into a cement slurry mixer and stirred to obtain a solid material; then the alkaline activator is added at a water-cement ratio of 0.4 and stirred rapidly for 4 minutes; the stirred slurry is poured into a 20×20×20 mm 3 In the six-unit test mold, vibrate on a vibration table for 1 minute, scrape the surface flat, let it stand and seal it with plastic wrap for 1 day, then demould and cure it to the specified age under the conditions of temperature 20±2℃ and relative humidity>95%;

[0040] The granulated blast furnace slag is S95 grade slag, and its main components are CaO (40.03%), SiO2 (33.58%) and Al2O3 (14.59%).

[0041] Example 2

[0042] This embodiment relates to a method for adsorbing and solidifying heavy metal ions in wastewater, and also relates to a method for preparing a geopolymer gelling material, comprising the following steps:

[0043] (1) grinding cement naturally cured for 7 days in a ball mill to a particle size of less than 125 μm to obtain concrete powder, wherein the concrete powder has a CaO content of 48.28%, a SiO2 content of 15.27%, and an Al2O3 content of 4.32%, and then carbonizing the concrete powder for 7 days under the conditions of a humidity of 70±3%, a temperature of 20±2° C., and a carbon dioxide concentration of 20±3%, wherein the grayish white concrete powder is transformed into pure gray carbonized concrete powder after carbonization; The carbonized concrete powder and the lead-containing wastewater are added into a glass container at a ratio of 10 g:1 L, the concentration of lead ions in the wastewater is 2000 mg / L, and the mixture is shaken at 25° C. and 200 rpm for 10 minutes in a shaker, and then filtered in a vacuum filtration device using a 30 μm PP polypropylene filter membrane to obtain powder and treated wastewater, the filtered carbonized concrete powder adsorbing lead ions is dried in an oven at 60° C. for 4 hours, and the treated wastewater is used to test the concentration of heavy metal ions;

[0044] (2) water, NaOH and water glass are mixed to prepare an alkaline activator with a modulus of 1.2 and a Na2O content of 4%, and the mixture is allowed to stand for 24 hours for use; the carbonized concrete powder adsorbing lead ions and granulated blast furnace slag dried in step (1) are added to a cement slurry mixer with equal weight (50%:50%, wherein theoretically, heavy metals account for about 8.5% of the ash mass) to obtain a solid material; then the alkaline activator is added at a water-cement ratio of 0.45 and stirred rapidly for 4 minutes; the evenly stirred slurry is poured into a 20×20×20mm 3 In the six-unit test mold, vibrate on a vibration table for 1 minute, scrape the surface flat, let it stand and seal it with plastic wrap for 1 day, then demould and cure it to the specified age under the conditions of temperature 20±2℃ and relative humidity>95%;

[0045] The granulated blast furnace slag is S95 grade slag, and its main components are CaO (40.03%), SiO2 (33.58%) and Al2O3 (14.59%).

[0046] Example 3

[0047] This embodiment relates to a method for adsorbing and solidifying heavy metal ions in wastewater, and also relates to a method for preparing a geopolymer gelling material, comprising the following steps:

[0048] (1) grinding cement naturally cured for 7 days in a ball mill to a particle size of less than 125 μm to obtain concrete powder, wherein the concrete powder has a CaO content of 48.28%, a SiO2 content of 15.27%, and an Al2O3 content of 4.32%, and then carbonizing the concrete powder for 7 days under the conditions of a humidity of 70±3%, a temperature of 20±2° C., and a carbon dioxide concentration of 20±3%, wherein the grayish white concrete powder is transformed into pure gray carbonized concrete powder after carbonization; The carbonized concrete powder and the lead-containing wastewater are added into a glass container at a ratio of 10 g:1 L, the concentration of lead ions in the wastewater is 2000 mg / L, and the mixture is shaken at 25° C. and 200 rpm for 10 minutes in a shaker, and then filtered in a vacuum filtration device using a 30 μm PP polypropylene filter membrane to obtain powder and treated wastewater, the filtered carbonized concrete powder adsorbing lead ions is dried in an oven at 60° C. for 4 hours, and the treated wastewater is used to test the concentration of heavy metal ions;

[0049] (2) water, NaOH and water glass are mixed to prepare an alkaline activator with a modulus of 1.2 and a Na2O content of 4%, and the mixture is allowed to stand for 24 hours for use; the carbonized concrete powder adsorbing lead ions dried in step (1) is added to a cement slurry mixer at a mass ratio of 2:7:1 (theoretically, heavy metals account for about 3.33% of the ash mass) to obtain a solid material; then the alkaline activator is added at a water-cement ratio of 0.4 and stirred rapidly for 4 minutes; the evenly stirred slurry is poured into a 20×20×20 mm 3 In the six-unit test mold, vibrate on a vibration table for 1 minute, scrape the surface flat, let it stand and seal it with plastic wrap for 1 day, then demould and cure it to the specified age under the conditions of temperature 20±2℃ and relative humidity>95%;

[0050] The granulated blast furnace slag is S95 grade slag, and its main components are CaO (40.03%), SiO2 (33.58%) and Al2O3 (14.59%);

[0051] The gypsum is phosphogypsum, and its main components are CaO (38.26%), SiO2 (7.52%) and SO3 (49.17%).

[0052] Performance Testing

[0053] 1. Adsorption capacity

[0054] Pb(NO3)2 (160 mg / 200 mg) was added to 100 mL of deionized water to simulate heavy metal wastewater, and the mixture was shaken in a shaker at 25 °C and 200 rpm for 10 minutes. The powder and the treated wastewater were then filtered using a 30 μm PP filter membrane in a vacuum filtration device. The treated wastewater was analyzed for Pb by inductively coupled plasma optical emission spectrometry (ICP-OES). 2+ concentration, adsorption capacity of heavy metal ions (Q e ) is calculated as:

[0055]

[0056] In the formula, Q e is the average adsorption amount (mg / g); C0 and C e are the initial heavy metal ion concentration and equilibrium heavy metal ion concentration (mg / L), respectively; V is the volume of the solution (L), and m is the mass of CRP (g);

[0057] The calculation formula of adsorption rate Ae (%) is:

[0058]

[0059] In the formula, C0 and C eare the initial heavy metal ion concentration and equilibrium heavy metal ion concentration (mg / L), respectively.

[0060] 2. Compressive strength

[0061] The geopolymer material specimen prepared in the embodiment and cured to the curing age under standard conditions is placed on the test bench of the constant load cement flexural and compressive testing machine with a contact area of ​​400mm. 2 The loading rate is 0.1 mm / min until the solidified body is destroyed. The compressive strength of the solidified body is P (MPa) = F / A, where F is the peak load at failure and A is the compressive area. The compressive strength test is carried out by three parallel measurements and the average value is taken.

[0062] 3. Toxic leaching

[0063] After the specimens were cured for 3 days, 7 days and 28 days, they were crushed and sieved to collect powders with a particle size of less than 200 μm. 2 g of powder was taken, 40 mL of acetic acid buffer extractant was added, and placed in a 100 mL polyethylene bottle. The bottle mouth was sealed and placed in a constant temperature oscillator with a speed of 120 rpm and a temperature of 24 ± 1 °C. The oscillation was performed for 18 hours. Subsequently, a needle filter was used to filter through a 0.45 μm filter membrane, and the clear liquid was collected in a test tube. After filtration, the filtrate was treated with concentrated nitric acid to reduce the pH value to below 2.0. The concentration of heavy metals in the leachate was measured by inductively coupled plasma optical emission spectrometry (ICP-OES).

[0064] The preparation method of the acetic acid buffer extractant is as follows: 5.7 mL of glacial acetic acid is added into deionized water, the volume is fixed to 1 L after mixing evenly, and the pH value of the solution is adjusted to 2.88±0.05.

[0065] Test Results

[0066] (1) The adsorption amount and adsorption rate of the adsorption solidification method described in Example 1-2 are shown in Table 1.

[0067] Table 1 Adsorption amount and adsorption rate of Example 1-2

[0068]

[0069] (2) The compressive strength data of the specimens prepared by the adsorption curing method described in Examples 1-3 are as follows: Figure 2 , Figure 3 , Figure 4 As shown, according to Figure 2 , Figure 3 and Figure 4 It can be seen that with the increase of curing age, the strength of the specimens gradually increases. After 3 days, 7 days and 28 days of curing, the strength can meet the construction requirements (greater than 10MPa).

[0070] (3) The leaching concentration is a key indicator for evaluating the curing and stabilization effect of geopolymers. The lower the value, the stronger the curing ability and stability of the geopolymer. The leaching concentration data of the test pieces prepared by the adsorption curing method described in Examples 1-3 are as follows: Figure 5 , Figure 6 , Figure 7 As shown, Figure 5 , Figure 6 , Figure 7 As shown in the figure, when the carbonized concrete powder is 2+ When the adsorption capacity reaches 200 mg / g, Pb 2+ The leaching concentration of Pb did not exceed the limit value (Pb < 5 mg / L) specified in the "Hazardous Waste Identification Standard - Leaching Toxicity Identification" (GB5085.3-2007). 2+ The curing rate of the geopolymer material exceeded 99%, further verifying the 2+ It has excellent curing ability and environmental stability. 2+ May be related to OH - Form hydroxyl coordination ions, generate stable heavy metal hydroxide precipitation, and seal in the gelling material of geopolymer. In addition, Pb 2+ It also reacts with Ca in the calcium sulfate produced by the alkali-activated reaction between C-(A)-SH and gypsum. 2+ Ion exchange occurs, it is incorporated into the silicate grid and adsorbed by calcium sulfate. At the same time, the formation of hydration products refines the pore structure of the material and reduces the migration path of heavy metal ions. These factors work together to improve the resistance to Pb 2+ adsorption and solidification ability.

[0071] Comparative Example 1

[0072] A method for treating wastewater and a method for preparing a geopolymer cementitious material are provided, which is the same as Example 1, except that slag and carbonized micropowder are mixed and stirred evenly to obtain a solid raw material, wherein the carbonized concrete micropowder accounts for 42%, the slag accounts for 50%, and the remaining 8% of lead nitrate is added in the form of a wastewater solution, and specifically comprises the following steps:

[0073] (1) grinding cement naturally cured for 7 days in a ball mill to a particle size of less than 125 μm to obtain concrete powder, wherein the concrete powder has a CaO content of 48.28%, a SiO2 content of 15.27%, and an Al2O3 content of 4.32%, and then carbonizing the concrete powder for 7 days under the conditions of a humidity of 70±3%, a temperature of 20±2° C., and a carbon dioxide concentration of 20±3%, wherein the off-white concrete powder is transformed into pure gray carbonized concrete powder after carbonization;

[0074] (2) water, NaOH and water glass are mixed to prepare an alkaline activator with a modulus of 1.2 and a Na2O content of 5%, and the mixture is allowed to stand for 24 hours for use; the carbonized concrete powder prepared in step (1) and granulated blast furnace slag are added to a cement slurry mixer in a ratio of (42%:50%) to obtain a solid material, and lead-containing wastewater is added, and then the alkaline activator is added to the remaining water at a water-cement ratio of 0.4, and the mixture is rapidly stirred for 4 minutes. The stirred slurry is poured into a 20×20×20 mm 3 The six-unit test mold was vibrated on a vibration table for 1 minute, the surface was scraped flat, allowed to stand and sealed with plastic wrap for 1 day, then demoulded and cured to the specified age under the conditions of temperature 20±2℃ and relative humidity>95%.

[0075] The test method for the compressive strength and leaching concentration of the specimen of Comparative Example 1 is consistent with that of Example 1.

[0076] Compared with Example 1, when lead-containing wastewater was directly added to Comparative Example 1, there was no compressive strength at all ages. This is because after directly adding Pb(NO3)2, the Pb dissolved by Pb(NO3)2 2+ It will react with sodium silicate and sodium hydroxide in the alkaline activator to form lead silicate and lead hydroxide flocculent products, which will eventually form insoluble precipitates after stirring, reducing the alkalinity of the solution, which will seriously hinder the progress of the alkaline activation reaction, resulting in poor fluidity, and will also hinder the dissolution of active Si and Al in the geopolymer precursor material and the [SiO4] and [AlO4] - Aggregation.

[0077] The leaching concentration of Comparative Example 1 is as follows Figure 8 shown; according to Figure 8 It can be seen that the leaching concentration of Comparative Example 1 is much higher than that of Example 1, and the leaching concentration of Comparative Example 1 is higher than the limit value after 3 days, and the leaching concentration after 28 days is also much higher than that of Example 1. This difference is mainly attributed to the direct dissolution of some Pb 2+ The hydroxide precipitates and complexes generated in alkaline environments are easily redissolved under acidic conditions, thereby increasing the Pb 2+ The amount of leaching.

[0078] Comparative Example 2

[0079] The solid raw material is obtained by mixing slag and carbide slag and stirring them evenly, wherein the slag accounts for 65% and the carbide slag accounts for 35%, and then adding 1.5% lead nitrate in the form of wastewater solution, which specifically includes the following steps:

[0080] Mix water, NaOH and water glass to prepare an alkaline activator with a modulus of 1.2 and a Na2O content of 5%. Let it stand for 24 hours for use. Add lead-containing wastewater, then add the remaining water of the alkaline activator at a water-cement ratio of 0.4, stir quickly for 4 minutes, and pour the stirred slurry into a 20×20×20mm 3 The six-unit test mold was vibrated on a vibration table for 1 minute, the surface was scraped flat, allowed to stand and sealed with plastic wrap for 1 day, then demoulded and cured to the specified age under the conditions of temperature 20±2℃ and relative humidity>95%.

[0081] The granulated blast furnace slag is S95 grade slag, and its main components are CaO (40.03%), SiO2 (33.58%) and Al2O3 (14.59%).

[0082] The main components of the carbide slag are CaO (89.5%), SiO2 (5.17%) and Al2O3 (2.99%).

[0083] The test methods for compressive strength and leaching concentration of the specimens in Comparative Example 2 are consistent with those in Example 1.

[0084] The compressive strength data of the specimens prepared by the adsorption curing method described in Comparative Example 2 are as follows: Fig. 9 As shown, according to Fig. 9 It can be seen that with the increase of curing age, the strength of the specimen gradually increases. After 3 days, 7 days and 28 days of curing, the strength cannot meet the construction requirements (greater than 10MPa). This is mainly because the Al2O3 and SiO2 contents of carbide slag are low, resulting in low alkali activation activity. After directly adding Pb(NO3)2, the Pb dissolved by Pb(NO3)2 2+ It will react with sodium silicate and sodium hydroxide in the alkaline activator to form lead silicate and lead hydroxide flocculent products, which will eventually form insoluble precipitates after stirring, reducing the alkalinity of the solution, which will seriously hinder the progress of the alkaline activation reaction, resulting in poor fluidity, and will also hinder the dissolution of active Si and Al in the geopolymer precursor material and the [SiO4] and [AlO4] - of aggregation.

[0085] The leaching concentration of Comparative Example 2 is as follows Fig.10 shown; according to Fig.10 It can be seen that the leaching concentration of Comparative Example 2 at 3 and 7 days is much higher than the limit, and the leaching concentration after 28 days is also much higher than that of Example 1. This difference is mainly attributed to the direct dissolution of some Pb 2+ The hydroxide precipitates and complexes generated in alkaline environments are easily redissolved under acidic conditions, thereby increasing the Pb 2+ The leaching amount is also related to the lower compressive strength caused by the lower activity of carbide slag.

[0086] Comparative Example 3

[0087] A geopolymer gelling material, the same as Example 1, except that the carbonized micropowder does not adsorb heavy metal ions:

[0088] (1) Concrete powder and its carbonization method are the same as in Example 1;

[0089] (2) water, NaOH and water glass are mixed to prepare an alkaline activator with a modulus of 1.2 and a Na2O content of 5%, and the mixture is allowed to stand for 24 hours for use; the carbonized concrete powder prepared in step (1) and granulated blast furnace slag are added in equal weights (50%:50%) into a cement slurry mixer and stirred to obtain a solid material; then the alkaline activator is added at a water-cement ratio of 0.4 and stirred rapidly for 4 minutes; the stirred slurry is poured into a 20×20×20 mm 3 In the six-unit test mold, vibrate on a vibration table for 1 minute, scrape the surface flat, let it stand and seal it with plastic wrap for 1 day, then demould and cure it to the specified age under the conditions of temperature 20±2℃ and relative humidity>95%;

[0090] The granulated blast furnace slag is the same as that in Example 1.

[0091] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention, rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A method for adsorbing and fixing heavy metal ions in water, characterized in that: The following steps are involved: (1) Adsorbing heavy metal ions in water with carbonized micropowder; the carbonized micropowder is obtained by carbonizing concrete micropowder in a carbon dioxide atmosphere, and the concrete micropowder is obtained by grinding hydrated cement; (2) mixing the carbonized micropowder after adsorbing heavy metal ions with one or more of granulated blast furnace slag, gypsum, and steel slag to obtain a solid material; (3) The solid material is mixed with an alkali activator and then cured and formed.

2. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: The heavy metal ions are one or more of lead ions, zinc ions and copper ions.

3. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: The particle size of the concrete powder is less than 125 μm.

4. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: Calculated by weight, the CaO content in the concrete fine powder is not less than 48.28%, the SiO2 content is not less than 15.27%, and the Al2O3 content is not less than 4.32%.

5. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: The carbonization conditions are: humidity 70±3%, temperature 20±2° C., carbon dioxide concentration 20±3%, and carbonization time 7 days.

6. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: The granulated blast furnace slag is S95 grade slag, and the median particle size D50 is 12.06 μm.

7. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: The mass proportion of the carbonized micropowder after adsorbing heavy metal ions in the solid material is 30-70%.

8. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: The alkaline activator comprises a mixture of sodium hydroxide solution and water glass, the modulus of which is 1-2 and the content of Na2O is 3-6wt%.

9. The method for adsorbing and fixing heavy metal ions in water according to claim 1, characterized in that: The water-cement ratio of the solid material to the alkali activator is 0.38-0.

45.

10. A geopolymer gelling material, characterized in that: The invention is prepared by the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Compound heavy metal solidifying agent for governing contaminated soil and preparation method thereof

    CN104479685A

  • Method for curing heavy metals in copper tailings by using industrial waste carbide slag and kaolin

    CN111995276A

  • High-valued treatment method of waste concrete recycled micro powder

    CN118754185A

  • Geopolymer material for curing various heavy metal ions and preparation method thereof

    CN118771796A

  • Carbonized regenerated aerated concrete adsorption material as well as preparation method and application thereof

    CN119098140A